Jerusalems Above and Below A Critique of J. L. Martyn's Interpretation of the Hagar–Sarah Allegory in Gal 4.21–5.1. - Byrne, Brendan 1939- (2014)
In several studies of Galatians, J. Louis Martyn has argued that in the allegory of Hagar and Sarah (4.1-5.1), the ‘two covenants’ of 4.24b, traditionally identified with Judaism and Christianity respectively, refer, on the one hand, to a Christian Jewish Law-observant Gentile mission, Teachers from whom are disturbing Paul's Galatian converts, and to the Law-free Gentile mission promulgated by Paul, on the other. In the light, particularly, of Paul's overall usage of ‘covenant’, Martyn's interpretation is not sustainable - though this need not imply a return to an anti-Jewish interpretation of the text.
Keywords: Galatians; Hagar–Sarah; Allegory; Covenant; mission slavery